2019
DOI: 10.1101/lm.048595.118
|View full text |Cite
|
Sign up to set email alerts
|

The role of trait anxiety in associative learning during and after an aversive event

Abstract: Trait anxiety is considered to be a risk factor for anxiety disorders. The aim of the present study was to investigate how trait anxiety affects associative learning during and after an aversive event in laboratory rats. For this, rats were first submitted to a light-dark box test, followed by relief, safety, and fear learning. Our data demonstrate that all types of learning were affected by trait anxiety, both on a group and on an individual level. Whereas high levels of anxiety impaired relief and safety lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
3
6
0
Order By: Relevance
“…As pointed out above, NPSR −/− mice express more trait anxiety and, interestingly, the increase of anxiety after fear conditioning in NPSR‐deficient mice is driven by the female mice . However, at least in male rats, increased trait anxiety is negatively correlated with safety learning . The present data suggests that stress pre‐exposure or higher trait anxiety (as shown in NPSR‐deficient mice) increases the stress reactivity of an individual, which may follow an inverted U‐shape association with safety learning.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…As pointed out above, NPSR −/− mice express more trait anxiety and, interestingly, the increase of anxiety after fear conditioning in NPSR‐deficient mice is driven by the female mice . However, at least in male rats, increased trait anxiety is negatively correlated with safety learning . The present data suggests that stress pre‐exposure or higher trait anxiety (as shown in NPSR‐deficient mice) increases the stress reactivity of an individual, which may follow an inverted U‐shape association with safety learning.…”
Section: Discussionsupporting
confidence: 74%
“…Reason for the observed sex difference could be that females often show higher trait anxiety than males [34][35][36][37] and that trait anxiety is negatively correlated with the "opponent" emotion safety. 38 Taken together, our first two experiments demonstrated that safety learning seems to be a very robust type of learning that cannot be impaired by pre-exposure to stress, at least with the protocol used here. Pre-exposure to immobilization stress did not affect behavior in the acclimation phase as well as safety learning per se.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Some of these changes are not only seen in clinical populations but also in human subjects with high but not yet pathological trait anxiety [ 24 , 25 , 26 ]. Of note, also rats with high trait anxiety showed exaggerated fear learning, a less specific fear memory, and impaired fear extinction [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%